2015
DOI: 10.1111/clr.12712
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective volume analysis of bone remodeling after tooth extraction with and without deproteinized bovine bone mineral insertion

Abstract: Grafting of the sockets with DBBM and a resorbable barrier insertion seemed to reduce negative osseous remodeling in the short term when compared to that of the ungrafted sockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(42 reference statements)
0
21
1
Order By: Relevance
“…Importantly, the baseline CBCT images were taken immediately after tooth removal. This eliminated the need of digital subtraction of pre‐extraction target teeth, as reported in previous studies (Abdelhamid, Omran, Bakhshalian, Tarnow, & Zadeh, ; Crespi et al., ; Sbordone et al., ), and had the advantage to avoid the superimposition of bone and dental tissue.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, the baseline CBCT images were taken immediately after tooth removal. This eliminated the need of digital subtraction of pre‐extraction target teeth, as reported in previous studies (Abdelhamid, Omran, Bakhshalian, Tarnow, & Zadeh, ; Crespi et al., ; Sbordone et al., ), and had the advantage to avoid the superimposition of bone and dental tissue.…”
Section: Discussionmentioning
confidence: 80%
“…, Sbordone et al. ). The use of autologous bone particles did not significantly alter the ridge resorptive process (Araújo & Lindhe, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of porcine xenograft seemed to be an effective strategy for preserving architecture of the alveolar ridge . As regards studies that employed the same slowly resorbable graft biomaterial, these reported at 4 to 6 months of clinical follow‐up an average loss of the alveolar height of 1 mm; whereas for the same healing period in the control group (non‐grafted), vertical bone loss ranged between 1 and 3.1 mm .…”
Section: Discussionmentioning
confidence: 99%